Status and Trends of Juvenile Crime in The Republic of Serbia - Vujičić, Nikola (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
Juvenile delinquency is one of the topics that deserves special attention from the scientific and professional public, since it is about dealing with those categories of offenders who are often labeled as particularly sensitive. In this paper, after pointing out the theoretical aspects of the subject matter and some of the numerous studies, primarily longitudinal and self-reported studies, the author presents the trends of juvenile crime in the Republic of Serbia from 2009 to 2018 (10-year section) based on official statistics and indicators, which are registered by the Statistical Office. Particular attention was paid to the reported and adjudicated crime, the type of criminal sanctions imposed by the court, and the comparison of juvenile crime with adult crime. Bearing in mind that in the last few years there has been a lot of talk about changes in criminal legislation in this matter, which are probably very certain, and in that sense many (un)verified statements are made regarding the increase in the number of registered offenses committed by juveniles, the purpose of this paper is to analyze the status and trends of juvenile crime in the Republic of Serbia by analyzing official data.